Pengembangan Alat Pembelajaran Pelontar Bola Dalam Permainan Tenis Meja - Rudiansyah; Fery Toding Allo (Yayasan Perguruan Kampus, 2023)
The development of learning tools for throwing balls in the game of table tennis is the aim of researchers to assist activities in table tennis practicum lectures. In table tennis lectures, especially during the practicum, forehand and backhand strokes are still done manually by the lecturer, so it takes longer, causing boredom. from students waiting in line. The research method used is the Research and development (R&D) research design method with the ADDIE development model (Tegeh and Kirna (2013) consisting of stages 1) Analysis, 2) Design, 3) Development (Development), 4) Implementation (Implementation) and 5) Evaluation (Evaluation). The result of the development carried out by researchers was the creation of table tennis ball throwing media which was obtained from several trials of applying this equipment. Development of learning media for throwing tennis balls The table for improving forehand and backhand skills has good quality to be used as a lecture support.